Electronically Tunable Differential Integrator: Linear Voltage Controlled Quadrature Oscillator. (19th April 2015) - Nandi, Rabindranath; Pattanayak, Sandhya; Venkateswaran, Palaniandavar; Das, Sagarika
Abstract : A new electronically tunable differential integrator (ETDI) and its extension to voltage controlled quadrature oscillator (VCQO) design with linear tuning law are proposed; the active building block is a composite current feedback amplifier with recent multiplication mode current conveyor (MMCC) element. Recently utilization of two different kinds of active devices to form a composite building block is being considered since it yields a superior functional element suitable for improved quality circuit design. The integrator time constant( τ ) and the oscillation frequency( ω o ) are tunable by the control voltage( V ) of the MMCC block. Analysis indicates negligible phase error( θ e ) for the integrator and low activeω o -sensitivity relative to the device parasitic capacitances. Satisfactory experimental verifications on electronic tunability of some wave shaping applications by the integrator and a double-integrator feedback loop (DIFL) based sinusoid oscillator with linearf o variation range of 60 KHz 1.8 MHz at low THD of 2.1% are verified by both simulation and hardware tests.